A Pilot Study on β-lactamase Producing Escherichia coli from Bovine Milk, West Bengal - S. Bandyopadhyay; D. Bhattacharyya; S. Saha; J. Banerjee; Md. Habib; C. Maji; D. Mondal; P. K. Nanda; A. K. Das (International Journal of Toxins and Toxics, 2024)
Drug resistant bacteria have become a significant global healthcare issue that requires close attention. With regards to antibiotic resistance, E.coli and its Enterobacteriaceae family are highly notorious for their ability to swiftly spread antibiotic resistance genes, thereby posing a major concern. In order to effectively address the spread of multi drug resistant bacteria, ongoing monitoring of the microflora in milk for the presence of drug resistant genes is essential. This continuous assessment will enable us to determine the frequency at which antibiotic resistant genes are found specifically in E.coli. As part of a recent study, a total of 288 E.coli colonies were isolated from bovine milk (n=144) to obtain a comprehensive understanding of the situation at hand. These isolates were thoroughly examined, resulting in the identification of multi drug resistance in a noteworthy percentage of the E.coli strains, specifically 24.3% of them. Further analysis to determine the types of resistance revealed that the majority of the resistance cases were attributed to blaAmpC type beta-lactamases, accounting for approximately 65.03% of the observed instances. Additionally, a smaller percentage of resistance genes were seen to belong to 4.14% of the for blaCTX-M and 7.14 % for blaTEM. It is important to note that roughly 42.85% of the E.coli isolates were found to be AmpC type beta-lactamase producers. These findings shed a brighter light on the prevalence of drug resistance among the microbial population in bovine milk, with an emphasis on the concerning presence of drug resistance in E.coli. By expanding our knowledge in this specific area, we can successfully develop effective strategies and interventions to effectively combat and prevent the spread of antibiotic resistance. Thus, it becomes apparent that addressing this issue is of utmost importance for the overall health and well-being of the global population.
Keywords: ACBL; Antibiotic resistance markers; ESBL; Enterobacteriaceae; Escherichia coli; MDR